The love of my life - Walsh, Rosie ([New York City] : Pamela Dorman Books/Viking, 2022)
Emma loves her husband Leo and their young daughter Ruby: she'd do anything for them. But almost everything she's told them about herself is a lie. And she might just have got away with it, if it weren't for her husband's job. Leo is an obituary writer; Emma a well-known marine biologist. When she suffers a serious illness, Leo copes by doing what he knows best - researching and writing about his wife's life.
"The Good Morning America book club, a GMA book club pick!"--Jacket.
Keywords: Married people -- Fiction; Secrecy -- Fiction; Identity (Psychology) -- Fiction; Detective and mystery fiction; Romance fiction